The Influence of Digital Financial Literacy, Financial Self-Efficacy, and Financial Experience on The Interest in Using Pay-Later Fintech Payment Services Among Students in Yogyakarta - Ardha Gunung Maenaka; Ratih Kusumawardhani; Risal Rinofah (Cakrawala Repositori IMWI)
The development of digital technology has encouraged the emergence of technology-based financial services, one of which is fintech pay-later services. While offering convenience and flexibility, the adoption of these services is not only influenced by technological factors, but also by individual factors such as digital financial literacy, self-efficacy in managing finances, and financial experience. However, there remains a research gap regarding which individual factors most dominantly influence students' interest in using pay-later services, particularly in the Indonesian context where fintech adoption is rapidly growing but consumer protection mechanisms are still developing. This study aims to analyze the influence of Digital Financial Literacy (DFL), Financial Self-Efficacy (FSE), and Financial Experience (FE) on the interest in using fintech payment pay-later in students in Yogyakarta. This study uses a quantitative method with a descriptive approach. The research sample amounted to 100 students who were selected using the purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results showed that simultaneously, the three independent variables had a significant effect on the interest in using pay-later. However, partially, only financial self-efficacy has a positive and significant effect. Meanwhile, digital financial literacy and financial experience have no significant effect on interest. These findings indicate that students' self-confidence in managing finances is more dominant in influencing their decision to use pay-later services compared to their financial knowledge and experience.